2012
DOI: 10.7314/apjcp.2012.13.7.3015
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Regulation of Manganese Superoxide Dismutase (MnSOD) on the Radiosensitivity of Esophageal Cancer Cells

Abstract: The mitochondrial antioxidant protein manganese superoxide dismutase (MnSOD) may represent a new type of tumor suppressor protein. Overexpression of the cDNA of this gene by plasmid or recombinant lentiviral transfection in various types of cancer leads to growth suppression both in vitro and in vivo. We previously determined that changes in MnSOD expression had bidirectional effects on adriamycin (ADR) when combined with nitric oxide (NO). Radiation induces free radicals in a manner similar to ADR, so we spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Previous studies also showed that overexpression of SOD2 in tumor cells can enhance radiosensitivity of tumor cells rather than act as a protector [12, 26, 27]. The relevant mechanism, which is unknown at present, may be the different redox state in tumor cells versus the normal cells [11, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also showed that overexpression of SOD2 in tumor cells can enhance radiosensitivity of tumor cells rather than act as a protector [12, 26, 27]. The relevant mechanism, which is unknown at present, may be the different redox state in tumor cells versus the normal cells [11, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on human tissue specimens showed that MnSOD was absent or reduced in breast cancer (Soini et al, 2001) and prostate cancer (Wang et al, 2006). Nevertheless, MnSOD overexpression to decrease ROS levels in the cells was able to reduce cell doubling time and plating efficiency of osteosarcoma cells, thus reducing its transfection rate Komatsu et al, 2005 ;Sun et al, 2012). MnSOD expression was also able to inhibit or reverse the malignant phenotype and growth of human fibroblast SV40 (Yan et al, 1996), malignant melanoma tumor (Zwacka et al, 1993), and glioma cells (Zhong et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…MnSOD is the important antioxidant agent in the mitochonderia that catalyzes the dismutation of superoxide radicals to hydrogen peroxide form and detoxification of mitochondrial ROS (Sun et al, 2012). The MnSOD gene as tumor suppressor gene is located on chromosome 6 at q25.3.…”
Section: Discussionmentioning
confidence: 99%